Anterior Segment Optical Coherence Tomography: Is There a Clinical Role in the Management of Primary Angle Closure Disease?. Issue 1 (January 2020) - Nongpiur, Monisha E.; Tun, Tin A.; Aung, Tin
Abstract : Primary angle closure disease (PACD) covers a spectrum that includes primary angle closure suspect, primary angle closure, primary angle closure glaucoma, and acute primary angle closure. Accumulating evidence suggests that the pathogenesis of PACD is complex, with multiple contributory factors including variations in the anatomic or biometric characteristics of the angle segment structures. Advances in anterior segment optical coherence tomography technology have further enhanced our understanding of the risk factors and mechanisms involved in the disease process. This review discusses the potential clinical role of the anterior segment optical coherence tomography in the diagnosis, mechanistic evaluation, and as a predictor for future clinical outcomes of patients with PACD.